2011
DOI: 10.1186/1471-244x-11-83
|View full text |Cite
|
Sign up to set email alerts
|

The clinical global impression scale and the influence of patient or staff perspective on outcome

Abstract: BackgroundSince its first publication, the Clinical Global Impression Scale (CGI) has become one of the most widely used assessment instruments in psychiatry. Although some conflicting data has been presented, studies investigating the CGI's validity have only rarely been conducted so far. It is unclear whether the improvement index CGI-I or a difference score of the severity index CGI-S dif is more valid in depicting clinical change. The current study examined the validity of these two measures and investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 25 publications
2
81
0
Order By: Relevance
“…Data were collected within the scope of a comprehensive research project (Forkmann, Forkmann et al, 2011;Scherer et al, 2013).…”
Section: Psychotherapy Researchmentioning
confidence: 99%
“…Data were collected within the scope of a comprehensive research project (Forkmann, Forkmann et al, 2011;Scherer et al, 2013).…”
Section: Psychotherapy Researchmentioning
confidence: 99%
“…36 The use of the CGI-C and CGI-S clinician rating efficacy measures have been previously compared. 37,38 Forkman et al reported comparable results between the CGI-C and CGI-S scales; however, they noted that both scales lacked congruence with patient ratings, and as a result, the authors suggested a variety of patient-and clinical-rated scales be incorporated in clinical trial designs.…”
Section: Discussionmentioning
confidence: 99%
“…3. Efficacy index: compares the patient's baseline condition to a ratio of current therapeutic benefit and severity of side effects (CGI-E) [8]. …”
Section: Methodsmentioning
confidence: 99%